Pengaruh Kepuasan Gaji, Kepuasan Kerja, Dan Komitmen Organisasional Terhadap Turnover Intention Pada PT. Bumi Menara Internusa Dampit - Firda Sukanti; Siti Asiyah; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study was to determine the effect of salary satisfaction, job satisfaction and organizational commitment to Turnover Intention at PT. BMI in Dampit City. Determination of the sample in this study is using saturated samples, so that the number of samples can be determined as many as 63 respondents according to the criteria. The analytical tool used in this research is multiple linear regression analysis. The results showed that salary satisfaction, job satisfaction and organizational commitment simultaneously had a significant effect on turnover intention at PT. BMI in Dampit City. Salary satisfaction variable has a significant and positive effect on turnover intention at PT. BMI in Dampit City. Job satisfaction variable has no effect on turnover intention at PT. BMI in Dampit City. Organizational commitment variable has a significant and negative effect on turnover intention at PT. BMI in Dampit City. Keywords: Effect of Salary Satisfaction, Job Satisfaction, and Organizational Commitment on Turnover Intention at PT. BMI in Dampit City.